Em busca das terras de Promissão- a difícil construção de sujeitos sociais e políticos no assentamento de sem-terra de Promissão-SP - Barbosa, Maria de Fatima Silva (2005)
Abstract The objective of this dissertation aims to analyze the trajectory of a parcel of the urban social movements of Campinas (SP), that, in middle of the years 1980, decides “to leave the city” and to go in search of the “terras de Promissão” (Promised Lands). Known as “Campinas Group”, these social and political subjects engaged themselves in the MST – Movimento dos Trabalhadores Rurais Sem-Terra –, having as their project “to go back to the roots” through the conquest of the land, in the greater scope of the fight for the Agrarian Reform. The occupation of the “Reunidas” Farm in the city of Promissão (SP), main point of the action of the “Campinas Group”, gives origin to the largest land occupation of the state of São Paulo. This work recovers the trajectory and the history of protagonism and of challenges that permeates the action of the “Campinas Group”. This implies a narrative that points to its insertion in the urban popular movements in the region of Campinas, in the years 1970/80, to the exit of the families for the occupation of the “Reunidas” Farm, to the process that involved the organization of the land occupation, to the implantation of the Cooperativa de Produção Agropecuária “Padre Josimo Tavares” – COPAJOTA –, until arriving at the set of experiences and social-political and economic conflicts that occured in the production organization, in the practices and experiences of struggles and in the divisions and differentiated visions. When pointing to the peculiarities of the struggles of the “Campinas Group”, this dissertation stresses the intricacies of the difficult construction of social and political subjects in search of “writing their own history”.